PEMANFAATAN KERTAS ORIGAMI SEBAGAI MEDIA PEMBELAJARAN DALAM MENINGKATKAN KREATIFITAS ANAK USIA DINI DI TK AL-FIKH ORCHAD PENDAMAR MALAYSIA - Khoirunnisa Br Nainggolan, Farilah; Pasaribu, Munawir (LPPM IAD Probolinggo, 2024)
This research aims to explore the use of origami paper as a learning medium in developing the creativity of children aged 5-6 years in Tadika Al Fikh Orchad Pendamar, Malaysia. The research method used is descriptive qualitative, with data collection through observation and document analysis. The research results show that Tadika Al Fikh Orchad Pendamar applies a holistic educational approach which includes aspects of formal learning and the formation of moral and spiritual values. With professional teaching staff and various supporting facilities, this school has succeeded in creating a fun and effective learning atmosphere. The use of origami paper as a learning medium shows the school's commitment to providing innovative and interesting learning methods for students. In conclusion, a holistic approach to education, supported by creative learning media such as origami paper, plays an important role in improving the quality of learning and development of early childhood. keywords: Origami, learning, creativity